2022
DOI: 10.1177/07356331221074300
|View full text |Cite
|
Sign up to set email alerts
|

Lexiland: A Tablet-based Universal Screener for Reading Difficulties in the School Context

Abstract: Massive and timely screening of the student population for early signs of reading difficulties is needed to implement timely effective remediation of these difficulties. However, traditional approaches are costly and hard to apply. Here we present Lexiland, a tablet-based reading assessment tool for kindergarten and primary school children developed to be applied in school settings with minimal personnel intervention. Following a story line, players help a character of the game perform several tasks that measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…All tasks were presented digitally through individual tablets, except for reading and RAN. In order to do so, we created an Android-based application in videogame format, called Lexiland (Zugarramurdi et al, in press). Instructions and stimuli were prerecorded and delivered though headphones.…”
Section: Methodsmentioning
confidence: 99%
“…All tasks were presented digitally through individual tablets, except for reading and RAN. In order to do so, we created an Android-based application in videogame format, called Lexiland (Zugarramurdi et al, in press). Instructions and stimuli were prerecorded and delivered though headphones.…”
Section: Methodsmentioning
confidence: 99%
“…During kindergarten, most children (n = 33) could not read any of the presented words and pseudowords, and three children had already started learning how to read (they could read 9 out of 15 pseudowords, on average). At the end of first grade, mean reading accuracy was 0.75 (SD = 0.32, min = 0, max = 1) and reading scores displayed a bimodal distribution (see Zugarramurdi et al, 2021 for a broader description). Based on a -1 z score threshold, children were divided into two groups: poor readers (PR, mean accuracy = 0.13, min = 0, max = 0.45, n = 7) and typical readers (TR, mean accuracy = 0.89, min = 0.7, max = 1, n = 29).…”
Section: Topographymentioning
confidence: 99%
“…Forty children attending kindergarten (K5) took part in the study (21 males, age range 5 -6.5 years, mean = 6.1). These were selected as part of a larger study on reading acquisition (reported in Zugarramurdi et al, 2021Zugarramurdi et al, , 2022. All participants' caregivers provided informed written consent and all children verbally agreed to participate.…”
Section: Samplementioning
confidence: 99%